MENYEMBUNYIKAN INFORMASI RAHASIA PADA CITRA BITMAP MENGGUNAKAN METODE BIT PLANE COMPLEXCITY SEGMENTATION - I Wayan Simpen (CCIT Journal, 2012)
With the growing popularity of digital media, attention to the level of security becomes increasingly important. One important issue is the security level of the delivery of information. This can be done using encryption or steganography. Steganography is a method to insert a piece of confidential information in an object other media. Data hiding in steganography and cryptography are very different. If the cryptography, data that was encrypted (ciphertext) remain available, then the steganography, the ciphertext can be hidden so that third parties do not know it existed. In this project, the proposed media is the use of media such as image files JPG, GIF and BMP as input data a secret message carrier (carrier file). By using the method Compexcity Bit Plane Segmentation and DES encryption algorithms expect data confidentiality is guaranteed. The results of this project is to prove a technique of hiding secret messages in the media image. After going through the process and embeding data extraction process again from the stego file, confidential information may be disclosed again without damage or loss ofinformation.